La investigación científica es deficiente entre residentes de nefrología: el caso peruano - Herrera Añazco, Percy (2015)
Introduction: Clinical work can influence time spent on scientific research among physicians training in Nephrology. Objective: To describe scientific research practices among medical residents and specialists in Nephrology recently graduated in Peru. Material and Methods: We carried out a cross-sectional study on residents of nephrology of the last two years and specialists graduated from the past two years at the national level through a self-administered validated questionnaire. Results: We obtained 40 responses of which 50% were residents. 68% of respondents never conducted research during residency training. None of the respondents who performed some research work published their research. Almost all considered deficient their research training received and studies done in their hospitals. Conclusion: Scientific research practices among nephrology resident training in Peru are deficient. Strategies are needed to promote and develop it.